Global Melting Down: Us Vs the Rest of the World - Dhinesh Babu, S. (Prabandhan: Indian Journal of Management, 2010)
The underlying causes leading to the crisis had been reported in business journals for many months before September 2008, with commentary about the financial stability of leading U.S. and European investment banks, insurance firms and mortgage banks consequent to the subprime mortgage crisis. Beginning with failures caused by misapplication of risk controls for bad debts and collateralization of debt insurance, large financial institutions in the United States and Europe faced a credit crisis and a slowdown in economic activity. The impacts rapidly developed and spread into a global shock resulting in a number of European bank failures and declines in various stock indexes, and large reductions in the market value of equities. The credit crisis was exacerbated by Section 128 of the Emergency Economic Stabilization Act of 2008 which allowed the Federal Reserve to pay interest on excess reserve requirement balances held on deposit from banks, removing the incentive for banks to extend credit instead of placing cash on deposit with the FRB. Moreover, the de-leveraging of financial institutions further accelerated the liquidity crisis, and a decrease in international trade. World political leaders and national ministers of finance and central bank directors have coordinated their efforts to reduce fears but the crisis is ongoing and continues to change, developing at the close of October into a currency crisis with investors transferring vast capital resources into stronger currencies such as the yen, the dollar and the Swiss franc, leading many emergent economies to seek aid from the International Monetary Fund.